Cell Cycle Target Protein Induced by Galangin Treatment in Luminal Cells Confirmed by Bioinformatics Analysis - Sekarini, Diyah Novi; Jati, Yohanes Surya; Zulkepli, Nur Ayunie; Putri, Dyaningtyas Dewi Pamungkas (HAYATI Journal of Biosciences, 2025)
Galangin has activity modulating cell cycle arrest on luminal cancer cells and has high selectivity and low cytotoxicity for normal cells. This research intends to know galangin's prospective targets for promoting cell cycle arrest in luminal breast cancer via experimental in vitro, network pharmacology, and bioinformatics validation. In this research, MCF-7, a luminal model cell, was treated with galangin dose-dependent. Consequently, galangin exhibited a cytotoxic impact, with IC50 values of 117.86 μM. After that, SwissTargetPrediction, UALCAN, ShinyGO, and OncoLnc were used for bioinformatics validations, and Cytoscape software and the STRING website were used for computational analysis. Eight overlapping galangin target genes against luminal breast cancer were found. According to the analysis of the protein-protein interaction (PPI) network, eight hub genes-including CDK1, PLK1, TOP2A, ESR1, AURKB, NEK2, MMP9, and CA12-had the highest degree of freedom. Cell cycle regulation has been discovered to be tightly associated with overexpression of CDK1, PLK1, AURKB, and NEK2. By influencing the cell cycle, galangin inhibits the growth of luminal breast cancer, as determined by GO and KEGG enrichment analyses. In conclusion, by triggering cell cycle arrest, galangin may be used as a prospective chemotherapeutic treatment.